PENGARUH PIJAT BAYI TERHADAP DURASI MENYUSU ASI PADA BAYI USIA 0-3 BULAN DI KLINIK DR.CARE MOM AND BABY SPA KOTA SAMARINDA - agustantias, putrinda; Masyita, Gita; Meihartati, Tuti; Astutik, Widya (ITKES Wiyata Husada Samarinda, 2026)
Background: The impact of not giving exclusive breast milk to babies can result in problems with growth disorders (Grow Faltering) in children from the age of 1 to 3 months in Indonesia, according to the Ministry of Health's Indonesian Nutritional Status Study (SSGI) survey, explained Annas, prevalence Growth disruption in Samarinda City reached 22.8 percent. There are policy programs that are attempting to reduce the number of cases of growth disorders, such as ensuring the fulfillment of nutritional intake evaluated every year. Hence, this research is essential in lowering growth disorders hindering babies' weight gain. Baby massage is one solution to increase the duration of breastfeeding for babies. Purpose: This study aimed to determine the effect of baby massage on the duration of breastfeeding in babies aged 0-3 months at the Dr.Care Mom and Baby Clinic, Samarinda. Method: This study was a pre-experimental design with a one-group pretest-posttest design, namely assessing the effect of baby massage on the duration of breastfeeding at the age of 0-3 months at the Dr.Care Mom And Baby Spa clinic, Samarinda. The researcher determined the sampling method using the Lemeshow method with a non-probability sampling technique. The researcher sampled the respondents according to the researcher's desired criteria and used the Lemeslow formula of 30 respondents to calculate. Results: The results of the Wilcoxon statistical test showed that P-value < α where P-value (0.000) < α (0.05), namely that there was an effect of giving baby massage on the duration of breastfeeding in babies aged 0-3 months at the Dr.Care Clinic Mom And Baby Spa Samarinda. Conclusion: This indicates the influence of giving baby massage on the duration of baby breastfeeding at the Dr.Care Mom and Baby Spa Clinic, Samarinda.